University students’ subjective experiences with problem-based learning and associated generic skills - Ahram Lee; Eunju Jung (Frontiers in Psychology, 2025)
IntroductionWith the rapid change in society and advancements in technology, higher education needs to focus on cultivating students’ generic skills to foster adaptability in this ever-evolving society. Problem-based learning (PBL) is acknowledged as an effective approach to engage students in self-directed, real-life-based learning experiences that enhance generic skills. The current study investigated how university students subjectively experienced PBL and explored generic skills associated with their learning.MethodsUniversity students’ reflection papers were used as document data for analysis. A total of 58 reflection papers were collected from three PBL courses offered at a 4-year university in Seoul, Korea, between 2022 and 2023. Students were provided with open-ended questions that prompted them to give detailed descriptions of their learning experiences during PBL. The content of the papers was analyzed using inductive thematic analysisFindingsThe analysis revealed four key themes related to students’ experiences with PBL: collaboration within the team, personal growth, higher-order thinking, and connection to the real world. Each theme included three sub-themes, and these themes were discussed in relation to associated generic skills.DiscussionThe findings offer insights into students’ experiences during the PBL process and highlight how these experiences foster the development of cross-cutting skills applicable to various domains of life. This study extends the existing body of research, which has largely focused on quantitative measures of specific competency changes through PBL, by inductively exploring students’ subjective experiences and deriving relevant generic skills.